Overview of Model Free Adaptive (MFA) Control Technology - Al Smadi Takialddin; Osman Ibrahim Al-Agha; Khalid Adnan Alsmadi (Institute of Advanced Engineering and Science, 2018)
Model-Free Adaptive (MFA) control is a technology that has made a major impact on the automatic control industry. MFA control users have successfully solved many industry-wide control problems in various applications and achieved significant economic benefits. Now, the challenge is extending the many advantages of MFA control technology to diverse and fragmented markets, which could benefit from its unique capabilities. Since single-loop MFA controllers can directly replace legacy PID controllers without the need for